Temporal progression of treatment performance in soil aquifer treatment systems: Role of microbial communities - Cristina Valhondo; Marta Casado; Lurdes Martinez-Landa; Marta Gual; Paola Sepúlveda-Ruiz; Monserrat Folch; Claudia Sanz; Laia Navarro-Martín; Adrià Sunyer-Caldú; Juan Cruz Carrizo; Paula Rodríguez-Escales; Ruben Gil-Solsona; et al. (Water Research, 2026)

The Accumulation and Distribution of Green Synthesized Silver Nanoparticles with Açaí in C. elegans Do Not Cause Redox Toxicity - Andy Joel Taipe Huisa; Vivien Michaelis; Anna Gremme; Peter Niehaus; Uwe Karst; Lucie M. Lindenbeck; Adam Slabon; Christian W. Lehmann; Gürbüz Dursun; Guillaume Delaittre; José Maria Monserrat; Julia Bornhorst (Bulletin of Environmental Contamination and Toxicology, 2026)
Green synthesis of silver nanoparticles (AgNP) has been proposed as a safer and more sustainable alternative for AgNP production. However, limited information exists on the toxicity mechanisms and accumulation of green -synthesized AgNP. In this study, we used AgNP synthesized with Amazonian açaí (Bio-AgNP) to evaluate their accumulation and biochemical effects in Caenorhabditis elegans . Bio-AgNP were synthesized using aqueous extract of lyophilized açaí pulp as reducing and stabilizing agent. Caenorhabditis elegans N2 wild-type (L1 larvae) were exposed to 5 and 10 mg/L Bio-AgNP for 52 h. Silver accumulation and distribution were assessed, and GSH and GSSG levels quantified. Our results showed that Bio-AgNP accumulated in C. elegans (3.6 ± 0.5 and 17.9 ± 1.8 pg Ag/µg protein, respectively), distributed throughout the body, particularly in the midgut. However, no statistical significant changes in GSH or GSSG were detected. Overall, Bio-AgNP accumulate in C. elegans without affecting the GSH/GSSG redox balance, These findings support the potential of green chemistry as a sustainable pathway for nanoparticle production with reduced toxicological impact compared with AgNP produced by chemical synthesis.

Comparative analysis of nanosilver toxicity in C. elegans: influence of exposure media on accumulation, physiological and biochemical effects - Andy Joel Taipe Huisa; Marcelo Estrella Josende; Vivien Michaelis; Ann-Kathrin Weishaupt; Anna Gremme; Lucie M. Lindenbeck; Adam Slabon; Christian W. Lehmann; Gürbüz Dursun; Merve Seckin Altuncu; Guillaume Delaittre; José M. Monserrat; et al. (Environmental Science and Pollution Research, 2026)
Caenorhabditis elegans is widely used in nanotoxicology studies involving silver nanoparticles (AgNP). However, variations in test media composition can influence AgNP toxicity in worms, complicating cross-study comparisons. This study evaluated the effects of six commonly used media: M9 buffer, K-medium, S-basal, EPA water, Nematode Growth Medium agar (NGM), and “Biofilm” (a combination of NGM and EPA water) on biological responses in worms without the presence of AgNP and the toxicity and accumulation of citrate-coated AgNP (cit-AgNP). Our results indicate that, in the absence of AgNP, NGM and Biofilm were the least disruptive to worm size and DAF-16 translocation (p < 0.05), suggesting lower systemic stress responses. In contrast, all liquid media significantly affected at least one of these parameters. In the presence of cit-AgNP, toxicity patterns in C. elegans at 5 mg/L (administered in 1 mL of food source) varied across the tested media (EPA water, NGM, and Biofilm). Worms in EPA water exhibited the most pronounced effects on size, brood size, and GSH/GSSG levels, whereas those in NGM agar were unaffected. These differences are attributed to the media's impact on worms, observed for EPA water, and reduced Ag accumulation in worms due to increased Ag migration to agar, particularly in NGM. This study demonstrates that the treatment scenarios currently used for assessing AgNP toxicity in C. elegans produce varying outcomes due to the media’s intrinsic effects on worms and differences in Ag accumulation. Our findings underscore the need for standardized media to ensure accurate and comparable toxicity assessments.

Membrane effects in reinforced concrete: From experimental evidence to numerical and analytical modelling - Andrea Monserrat-López; Alejandro Nogales Arroyo; Duarte M. Viula Faria; Fabio Brantschen; Miguel Fernández Ruiz (Engineering Structures, 2026)

Community structure and microhabitat associations of cryptobenthic reef fishes in Veracruz, Mexico - Mariana Rivera-Higueras; Christopher R. Hemingson; Aurora de Monserrat Pouchoulen Alemán; Kyra Jean M. Cipolla; Philip M. Souza; Simon J. Brandl (Coral Reefs, 2025)

Climate warming and the persistence of buried ice in the Pyrenees: Multi-Proxy evidence from Clots de la Menera cirque (Andorra) - Marc Oliva; Josep Ventura; Valentí Turu; Xavier Ros; Anna Echeverria; Attila Çiner; M. Akif Sarıkaya; Claudia Pérez-Ramos; Julia García-Oteyza; Josep Maria Bonsoms; Oriol Monserrat; Pedro Espín-López; et al. (Quaternary Science Reviews, 2025)

Intact glycoconjugates from Taenia crassiceps excreted/secreted products ameliorate chemically induced colitis by modulating inflammation and strengthening adherens junctions - Yadira Ledesma-Soto; Ilse Chávez-Soto; Marissa Calderón-Torres; Andrea Monserrat Rodríguez-Lozoya; Jonadab E. Olguin; Luis B. Hernández-Portilla; César M. Flores-Ortíz; Fernando Candanedo; Miriam Rodriguez-Sosa; Sonia E. Hernández-Navia; Luis I. Terrazas (Inflammopharmacology, 2025)
Background Ulcerative colitis (UC) is a chronic inflammatory disease that is increasing in prevalence worldwide. Notably, helminth infections, known for their immunoregulatory properties, are inversely related to inflammatory conditions such as UC. Research has indicated that Taenia crassiceps infection can improve inflammatory-mediated diseases, including type 1 diabetes, experimental autoimmune encephalomyelitis, and colitis. Subsequent studies revealed that helminth-derived products can replicate the effects of complete infection in the context of inflammatory diseases; however, the mechanisms underlying these effects remain unclear. This study examined the impact of intact glycans from T. crassiceps excreted/secreted products (TcES) on host responses to dextran sodium sulfate (DSS)-induced colitis. Methods UC was induced by administering 4% DSS in the drinking water for 9 days. The mice were treated with intact TcES, glycan-depleted TcES, or protein-depleted TcES 2 days after colitis induction. Symptoms of the disease, along with immunologic and histopathological evaluations, were performed. Results Colitic mice that received intact TcES presented fewer disease symptoms and less histopathological damage. Intact TcES reduced the proinflammatory response while increasing the production of IL-4, IL-22, IL-31, and MCP-1 and promoting M2 macrophage polarization via PD-L2 expression. Furthermore, intact TcES diminished neutrophil infiltration, inhibited NF-κB and p38 phosphorylation in the colon, and suppressed reactive oxygen species and 3-nitrotyrosine levels, thus protecting the colon. These effects were accompanied by increased expression of E-cadherin and β-catenin, indicating improved epithelial barrier integrity. Conversely, mice treated with glycan-depleted or protein-depleted TcES exhibited exacerbated colitis characterized by disruption of colon tissue architecture, extensive inflammation, and epithelial damage, including loss of E-cadherin and β-catenin and a lack of M2 macrophage polarization. Conclusions Glycoconjugates on TcES play a significant role in mediating the immunomodulatory effects that alleviate DSS-induced colitis.

Applications of UAV Digital Photogrammetry in landslide emergency response and recovery activities: the case study of a slope failure in the A-7 highway (S Spain) - Jorge P. Galve; José L. Pérez-García; Patricia Ruano; José M. Gómez-López; Cristina Reyes-Carmona; Marcos Moreno-Sánchez; Paula S. Jerez-Longres; Mehrnoosh Ghadimi; Anna Barra; Rosa M. Mateos; Oriol Monserrat; José Miguel Azañón (Landslides, 2025)
The disruption of vehicle traffic on important transport infrastructure has a major economic impact. Therefore, the instability of highway cut-slopes poses a significant risk for major infrastructures crossing mountainous regions and rocky coasts. The use of Uncrewed Aerial Vehicles (UAVs) is of great help in the prevention of road cut-slope failures and in emergency and rehabilitation of sites impacted by this type of landslides. Here, we show an example of UAV operations in emergency response and recovery in a highway cut-slope failure. We analyzed a failure that occurred on 11 March 2021 in a 52-m-high cut-slope located at 354.3 km of the A-7 Highway (S Spain). We also examine the applications of these analyses to help in risk evaluation and management. We acquired 3050 images and 6 videos with UAVs during 5 field surveys from 11 to 31 March 2021 to follow the evolution of the destabilized cut-slope. The videos taken by UAVs were of great help in the emergency response phase to guide the first steps in the removal of unstable rock blocks. The acquired images served to generate sequential Digital Elevation Models (DEMs) and 3D models (i.e., point clouds and tiled models) using the Digital Photogrammetry technique. These models were used subsequently to identify changes in the topography and calculate volumes of both destabilized and excavated material. The volumetric analyses indicate that 6200 m 3 of rock collapsed, producing a deposit of debris of 10,900 m 3 , and after the partial failure, 15,100 m 3 of the slope remained unstable. Therefore, the volume of rock mobilized by the landslide was about 21,300 m 3 . The recovery activities involved the removal of the collapsed debris and the re-profiling of the slope. This involved the excavation, transportation, and deposition of 83,400 m 3 of rock to reduce the slope’s inclination from 64° to 45–33°. We then analyzed the follow-up work generating sequential DEMs during the cut-slope excavation in order to forecast the approximate date of the highway reopening. Thus, an average excavation speed of 1075 m 3 /day was estimated, and with this value, by March 31, it was possible to initially forecast that the highway could be reopened in the first week of June, not far from June 10, the date on which it was finally reopened. These results were obtained with reduced equipment costs and field time over topography conventional methods, which indicates the usefulness of UAVs and Digital Photogrammetry (UAV-DP) in emergency response and recovery situations provoked by unstable slopes in roads.

Performance of nodal regions of reinforced concrete frame corners subjected to opening bending moments - Andrea Monserrat-López; Duarte M. Viula Faria; Fabio Brantschen; Miguel Fernández Ruiz (Engineering Structures, 2025)

Sex differences in behavior, cognitive, and physiological recovery following methamphetamine administration - Monserrat Armenta-Resendiz; Jordan S. Carter; Zachariah Hunter; Makoto Taniguchi; Carmela M. Reichel; Antonieta Lavin (Psychopharmacology, 2024)
Intact executive functions are required for proper performance of cognitive tasks and relies on balance of excitatory and inhibitory (E/I) transmission in the medial prefrontal cortex (mPFC). Hypofrontality is a state of decreased activity in the mPFC and is seen in several neuropsychiatric conditions, including substance use disorders. People who chronically use methamphetamine (meth) develop hypofrontality and concurrent changes in cognitive processing across several domains. Despite the fact that there are sex difference in substance use disorders, few studies have considered sex as a biological variable regarding meth-mediated hypoactivity in mPFC and concurrent cognitive deficits. Hypofrontality along with changes in cognition are emulated in rodent models following repeated meth administration. Here, we used a meth sensitization regimen to study sex differences in a Temporal Order Memory (TOM) task following short (7 days) or prolonged (28 days) periods of abstinence. GABAergic transmission, GABAA receptor (GABA A R) and GABA Transporter (GAT) mRNA expression in the mPFC were evaluated with patch-clamp recordings and RT-qPCR, respectively. Both sexes sensitized to the locomotor activating effects of meth, with the effect persisting in females. After short abstinence, males and females had impaired TOM and increased GABAergic transmission. Female rats recovered from these changes after prolonged abstinence, whereas male rats showed enduring changes. In general, meth appears to elicit an overall decrease in GABA A R expression after short abstinence; whereas GABA transporters are decreased in meth female rats after prolonged abstinence. These results show sex differences in the long-term effects of repeated meth exposure and suggest that females have neuroprotective mechanisms that alleviate some of the meth-mediated cognitive deficits.

Metal-based nanomaterials in aquatic environments: What do we know so far about their ecotoxicity? - Analía Ale; Victoria S. Andrade; María Florencia Gutierrez; Alinne Ayech; José M. Monserrat; Martín F. Desimone; Jimena Cazenave (Aquatic Toxicology, 2024)

Determination of acute toxicity and evaluation of the chronic effect of nitrate on compensatory growth of Litopenaeus vannamei reared in a biofloc technology system - Elisa Prates; Marcelo Okamoto; Mariana Holanda; José M. Monserrat; Matthew James Slater; Wilson Wasielesky (Aquaculture, 2024)

Effect of a nutritional intervention based on an energy-reduced Mediterranean diet on environmental impact - Laura Álvarez-Álvarez; María Rubín-García; Facundo Vitelli-Storelli; Silvia García; Cristina Bouzas; Miguel Ángel Martínez-González; Dolores Corella; Jordi Salas-Salvadó; Mireia Malcampo; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; et al. (Science of The Total Environment, 2024)

From micro to mesoscale: Understanding the influence of macroalgal communities on Ostreopsis Schmidt blooms - M. Monserrat; V. Asnaghi; J. Verdura; L. Meroni; R. Lemée; A.M. Rossi; G. Romero; F. Priouzeau; M. Chiantore; L. Mangialajo (Harmful Algae, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Correction to: Effects of dietary inclusion of lyophilized açai berries (Euterpe oleracea) on growth metrics, metabolic and antioxidant biomarkers, and skin color of juvenile tambaqui (Colossoma macropomum) - Thamyres Vanessa N. da Silva; Camila F. dos Santos; Jessica M. L. dos Santos; Marcos J. Schmitz; Juan R. B. Ramírez; Marcelo F. Torres; Luis André L. Barbas; Luís A. Sampaio; Pablo E. Verde; Marcelo B. Tesser; José M. Monserrat (Aquaculture International, 2024)

Develop of agave syrup using emerging technology by ohmic heating - Monserrat Martínez-Zavala; Mario Cruz; Hector A. Ruiz; Rosa M. Rodríguez-Jasso; Juan Carlos Contreras; Alberto Antonio Neira-Vielma; Ruth Belmares (Food and Humanity, 2023)

Analysis of SAR-derived products to support emergency management during volcanic crisis: La Palma case study - P. Ezquerro; G. Bru; I. Galindo; O. Monserrat; J.C. García-Davalillo; N. Sánchez; I. Montoya; R. Palamà; R.M. Mateos; R. Pérez-López; E. González-Alonso; R. Grandin; et al. (Remote Sensing of Environment, 2023)

Effects of dietary inclusion of lyophilized açai berries (Euterpe oleracea) on growth metrics, metabolic and antioxidant biomarkers, and skin color of juvenile tambaqui (Colossoma macropomum) - Thamyres Vanessa N. da Silva; Camila F. dos Santos; Jessica M. L. dos Santos; Marcos J. Schmitz; Juan R. B. Ramírez; Marcelo F. Torres; Luis André L. Barbas; Luís A. Sampaio; Pablo E. Verde; Marcelo B. Tesser; José M. Monserrat (Aquaculture International, 2023)

Compensatory growth and energy reserves changes in the Pacific white shrimp (Litopenaeus vannamei) reared in different temperatures and under feed restriction in biofloc technology system (BFT) - Elisa Prates; Mariana Holanda; Virgínia Fonseca Pedrosa; José M. Monserrat; Wilson Wasielesky (Aquaculture, 2023)

Wide-Geographic and Long-Term Analysis of the Role of Pathogens in the Decline of Pinna nobilis to Critically Endangered Species - Amalia Grau; Antonio Villalba; José I. Navas; Beatriz Hansjosten; José M. Valencia; José R. García-March; Patricia Prado; Guillermo Follana-Berná; Titouan Morage; Maite Vázquez-Luis; Elvira Álvarez; Pantelis Katharios; et al. (Frontiers in Marine Science, 2022)
A mass mortality event (MME) affecting the fan mussel Pinna nobilis was first detected in Spain in autumn 2016 and spread north- and eastward through the Mediterranean Sea. Various pathogens have been blamed for contributing to the MME, with emphasis in Haplosporidium pinnae , Mycobacterium sp. and Vibrio spp. In this study, samples from 762 fan mussels (necropsies from 263 individuals, mantle biopsies from 499) of various health conditions, with wide geographic and age range, taken before and during the MME spread from various environments along Mediterranean Sea, were used to assess the role of pathogens in the MME. The number of samples processed by both histological and molecular methods was 83. The most important factor playing a main role on the onset of the mass mortality of P. nobilis throughout the Mediterranean Sea was the infection by H. pinnae . It was the only non-detected pathogen before the MME while, during MME spreading, its prevalence was higher in sick and dead individuals than in asymptomatic ones, in MME-affected areas than in non-affected sites, and it was not associated with host size, infecting both juveniles and adults. Conversely, infection with mycobacteria was independent from the period (before or during MME), from the affection of the area by MME and from the host health condition, and it was associated with host size. Gram (-) bacteria neither appeared associated with MME.

Bioactivity of the Protein Hydrolysates Obtained from the Most Abundant Crustacean Bycatch - Tavani R. Camargo; Paulo Mantoan; Patrícia Ramos; José M. Monserrat; Carlos Prentice; Célio C. Fernandes; Willian F. Zambuzzi; Wagner C. Valenti (Marine Biotechnology, 2021)

Dietary Euterpe oleracea Mart. attenuates seizures and damage to lipids in the brain of Colossoma macropomum - Thamyres V. N. da Silva; Marcelo F. Torres; Luís A. Sampaio; Moisés Hamoy; José M. Monserrat; Luis André L. Barbas (Fish Physiology and Biochemistry, 2021)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Remote analysis of an open-pit slope failure: Las Cruces case study, Spain - Juan López-Vinielles; Pablo Ezquerro; José A. Fernández-Merodo; Marta Béjar-Pizarro; Oriol Monserrat; Anna Barra; Pablo Blanco; Javier García-Robles; Antón Filatov; Juan C. García-Davalillo; Roberto Sarro; Joaquín Mulas; et al. (Landslides, 2020)

The effects of co-exposure of graphene oxide and copper under different pH conditions in Manila clam Ruditapes philippinarum - Roberta Socoowski Britto; Jefferson Patrício Nascimento; Tiago Serode; Adelina P. Santos; Amadeu M. V. M. Soares; Etelvina Figueira; Clascídia Furtado; Juliane Lima-Ventura; José M. Monserrat; Rosa Freitas (Environmental Science and Pollution Research, 2020)

Zootechnical performance, biochemical response, and chromaticity in Pacific white shrimp (Litopenaeus vannamei) (Boone, 1931) after the inclusion of lyophilized açaí (Euterpe oleracea) in the diet - Shadai M. Silva; Patricia B. Ramos; Juan R. Buitrago; Thamyres V. N. da Silva; Cleber S. Simião; Grecica M. Colombo; Marcos Schmitz; Marcelo B. Tesser; Carlos Prentice; Wilson Wasielesky; José M. Monserrat (Aquaculture International, 2020)

Phylogeny of Pseudocercospora griseola from Puerto Rico, Central America and Tanzania confirms the existence of an Afro-Andean clade - Luz M. Serrato-Diaz; Edwin D. Navarro-Monserrat; Juan C. Rosas; Luseko A. Chilagane; Paul Bayman; Timothy G. Porch (European Journal of Plant Pathology, 2020)

Hippocampal place cells are topographically organized, but physical space has nothing to do with it - Thiago F. A. França; José M. Monserrat (Brain Structure and Function, 2019)

Forcing Factors Affecting Sea Level Changes at the Coast - Philip L. Woodworth; Angélique Melet; Marta Marcos; Richard D. Ray; Guy Wöppelmann; Yoshi N. Sasaki; Mauro Cirano; Angela Hibbert; John M. Huthnance; Sebastià Monserrat; Mark A. Merrifield (Surveys in Geophysics, 2019)

Protein oxidation in the fish Danio rerio (Cyprinidae) fed with single- and multi-walled carbon nanotubes - André L. R. Seixas; Marlize Ferreira-Cravo; Ana C. Kalb; Luis A. Romano; Claudir G. J. R. Kaufmann; José M. Monserrat (Energy, Ecology and Environment, 2018)

Effects of lipoic acid on growth and biochemical responses of common carp fed with carbohydrate diets - R. A. Santos; S. Caldas; E. G. Primel; M. B. Tesser; J. M. Monserrat (Fish Physiology and Biochemistry, 2016)

Unveiling the influence of the environment on the migration pattern of the Atlantic pomfret ( Brama brama ) in North‐eastern Atlantic waters - M. Quinzán; J. Castro; M. Marín; G. Costas; S. Monserrat; A. Amores; E. Massutí; M. Hidalgo (Fisheries Oceanography, 2016)
Hydroclimatic variability is one of the main factors that drives inter‐annual changes in fish migration patterns. This study analyses the relationship between climate‐oceanographic factors and migration of the Atlantic pomfret ( Brama brama ) in NE Atlantic waters. Geo‐referenced catch data from logbooks of longliners operating in European Atlantic waters from 2002 to 2013 were linked to environmental indices at different temporal and spatial scales. Our results point to a strong influence of temperature at 200 m depth as the key factor along with the upwelling in the Galician ( NW Iberian) waters. However, sea surface temperature ( SST ) indirectly affects the geographical display of Atlantic pomfret migration, and large migrations are observed in scenarios of high SST s in the migratory area ( c . above 14.7°C). Migrations are constrained during years when temperatures are below this threshold. A longer time‐series of annual landings (1950–2013) supports this evidence and highlights the significant influence of temperature at 200‐m depth along with the landings of the previous year. Length frequency distributions suggest an increase in size between consecutive seasons supporting the hypothesis that migration is a feeding strategy and a return to tropical waters of origin for spawning. Our study shows that the temperature of intermediate waters is a key variable in determining the northward migration of the Atlantic pomfret whereas density‐dependence and surface climatic conditions trigger secondary effects on the migration pattern of this species.

Tidal influence on high frequency harbor oscillations in a narrow entrance bay - S. Monserrat; I. Fine; A. Amores; M. Marcos (Natural Hazards, 2014)

Atmospheric processes responsible for generation of the 2008 Boothbay meteotsunami - I. Vilibić; K. Horvath; N. Strelec Mahović; S. Monserrat; M. Marcos; Á. Amores; I. Fine (Natural Hazards, 2014)

INFLUENCE OF CROP SPATIAL VARIABILITY WHEN CALCULATING IRRIGATION NETWORK FLOWS - J. Monserrat; M. Ezpeleta; M.A. Colomer; LL. Cots; J. Barragan (Irrigation and Drainage, 2013)
In on‐demand irrigation network design, calculation of pipe flows is usually based on the mean water requirements of the crops that can be expected to be planted in the area. However, while the network is sized for mean water needs, the actual requirements of each plot will depend on the crop planted and may well be different from the calculated mean water needs. As a result, the network may be undersized in terms of covering the flow demands of certain of its sections. The aim of this work was to study the influence of the spatial variability of crops on network flows and to make recommendations for methods of calculation capable of providing more reliable values for these flows. An equation was obtained that made it possible to determine what is known as the operation quality (OQ) based on the section number and the coefficient of variation of the water needs of the crops planned for the area. This equation was applied to two networks with different plot sizes and the results were compared with others obtained when the mean water requirements were assumed. Copyright © 2013 John Wiley & Sons, Ltd.

Accumulation, biotransformation, and biochemical responses after exposure to arsenite and arsenate in the estuarine polychaete Laeonereis acuta (Nereididae) - Juliane Ventura-Lima; Patrícia Baptista Ramos; Daniele Fattorini; Francesco Regoli; Luis Ferraz; Leandro Machado de Carvalho; José M. Monserrat (Environmental Science and Pollution Research, 2011)

Biologic Responses of Bacteria Communities Living at the Mucus Secretion of Common Carp (Cyprinus carpio) After Exposure to the Carbon Nanomaterial Fullerene (C60) - Rafaela Elias Letts; Talita C. B. Pereira; Mauricio Reis Bogo; José M. Monserrat (Archives of Environmental Contamination and Toxicology, 2011)

Systemic antioxidant properties of L-carnitine in two different models of arterial hypertension - Alfonso Mate; José L. Miguel-Carrasco; María T. Monserrat; Carmen M. Vázquez (Journal of Physiology and Biochemistry, 2010)

Results of a short study of interactions of cetaceans and longline fisheries in Atlantic waters: environmental correlates of catches and depredation events - Gema Hernandez-Milian; Sabine Goetz; Catuxa Varela-Dopico; José Rodriguez-Gutierrez; Jorge Romón-Olea; José R. Fuertes-Gamundi; Edelmiro Ulloa-Alonso; Nick J. C. Tregenza; Andy Smerdon; Monserrat G. Otero; Vicente Tato; Jianjun Wang; et al. (Hydrobiologia, 2008)

Estradiol valerate and tibolone: effects upon brain oxidative stress and blood biochemistry during aging in female rats - R. B. de Aguiar; O. E. Dickel; R. W. Cunha; J. M. Monserrat; D. M. Barros; P. E. Martinez (Biogerontology, 2008)

Phylogenetic relationships in Peniocereus (Cactaceae) inferred from plastid DNA sequence data - Salvador Arias; Teresa Terrazas; Hilda J. Arreola-Nava; Monserrat Vázquez-Sánchez; Kenneth M. Cameron (Journal of Plant Research, 2005)

p53 Expression in circulating lymphocytes of non-melanoma skin cancer patients from an arsenic contaminated region in Mexico. A pilot study - Ana M. Salazar; Emma Calderón-Aranda; Mariano E. Cebrián; Monserrat Sordo; Andrés Bendesky; Arístides Gómez-Muñoz; Leonor Acosta-Saavedra; Patricia Ostrosky-Wegman (Molecular and Cellular Biochemistry, 2004)

Determination of Lipid Peroxides in Invertebrates Tissues Using the Fe(III) Xylenol Orange Complex Formation - J. M. Monserrat; L. A. Geracitano; G. L. L. Pinho; T. M. Vinagre; M. Faleiros; J. C. Alciati; A. Bianchini (Archives of Environmental Contamination and Toxicology, 2003)

Ectopic Activity in Ventricular Cells Induced by Early Afterdepolarizations Developed in Purkinje Cells - Marta Monserrat; Javier Saiz; Jose M. Ferrero, Jr.; Jose M. Ferrero; Nitish V. Thakor (Annals of Biomedical Engineering, 2000)

Effect of MPTP on Brain Mitochondrial H2O2 and ATP Production and on Dopamine and DOPAC in the Striatum - E. Fabre; J. Monserrat; A. Herrero; G. Barja; M. L. Leret (Journal of Physiology and Biochemistry, 1999)

Short-term handling of the slimming agent oleoyl-estrone in liposomes (Merlin-2) by the rat - D. Sanchis; F. Balada; M.M. Grasa; J. Virgili; C. Monserrat; J.A. Fernández-López; X. Remesar; M. Alemany (Molecular and Cellular Biochemistry, 1997)

Aphidophagous predator diagnosis: Key to genera of European chrysopid larvae (Neur.: Chrysopidae) - L. M. Diaz-Aranda; V. J. Monserrat (BioControl, 1995)

Chronic toxicity of ethyl parathion and isobutoxyethanol ester of 2,4-dichlorophenoxyacetic acid to estuarine juvenile and adult crabs - Enrique M. Rodrguez; Jos M. Monserrat; Oscar A. Amn (Archives of Environmental Contamination and Toxicology, 1992)